Rational Design of Albumin Theranostic Conjugates for Gold Nanoparticles Anticancer Drugs: Where the Seed Meets the Soil? - Popova, Tatyana V.; Pyshnaya, Inna A.; Zakharova, Olga D.; Akulov, Andrey E.; Shevelev, Oleg B.; Poletaeva, Julia; Zavjalov, Evgenii L.; Silnikov, Vladimir N.; Ryabchikova, Elena I.; Godovikova, Tatyana S. (Biomedicines, 2021)
Multifunctional gold nanoparticles (AuNPs) may serve as a scaffold to integrate diagnostic and therapeutic functions into one theranostic system, thereby simultaneously facilitating diagnosis and therapy and monitoring therapeutic responses. Herein, albumin-AuNP theranostic agents have been obtained by conjugation of an anticancer nucleotide trifluorothymidine (TFT) or a boron-neutron capture therapy drug undecahydro-closo-dodecaborate (B12H12) to bimodal human serum albumin (HSA) followed by reacting of the albumin conjugates with AuNPs. In vitro studies have revealed a stronger cytotoxicity by the AuNPs decorated with the TFT-tagged bimodal HSA than by the boronated albumin conjugates. Despite long circulation time, lack of the significant accumulation in the tumor was observed for the AuNP theranostic conjugates. Our unique labelling strategy allows for monitoring of spatial distribution of the AuNPs theranostic in vivo in real time with high sensitivity, thus reducing the number of animals required for testing and optimizing new nanosystems as chemotherapeutic agents and boron-neutron capture therapy drug candidates.